EVALUASI STRATEGI GREEN MARKETING TERHADAP VOLUME PENJUALAN PRODUK PADA PLATFORM E-COMMERCE - Soraya Lestari; Lisnawati Lisnawati; Muji Usfari (Ubudiyah Indonesia University, 2025)
This study aims to determine how the evaluation of green marketing strategies affects product sales volume on e-commerce platforms. In the implementation of green marketing, four elements of the marketing mix are adopted, known to consist of the 4Ps are Product, Price, Place, and Promotion. Based on the philosophy of green marketing, each element in the marketing mix must have a green perspective in its marketing activities. Data collection techniques used in this study include observation, questionnaires, and documentation. The data analysis technique used is a quantitative approach with a sample size of 43 respondents. The results of the study show that, partially, green products have a positive and significant influence on product sales volume on e-commerce platforms. Similarly, green place is also proven to have a positive and significant effect on product sales volume on e-commerce platforms. However, green promotion and green price do not have a significant effect on product sales volume on e-commerce platforms. Nevertheless, simultaneously, green product, green price, green promotion, and green place have a significant effect on product sales volume on e-commerce platforms. Keywords: E-Commerce, Green Product, Green Price, Green Promotion, Green Place, MSMEs, Sales Volume